“Las tic como herramientas en el proceso intercultural de enseñanza-aprendizaje” - Correa Toapanta, Julia Verónica (2022)
This research is based on to promote the use of ICTs as a tool in the intercultural teaching-learning process in second grade students of General Basic Education at Emilio Terán school that is located in Cotopaxi province, Salcedo city, Mulliquindil parish during the 2021 - 2022 school year. The main objective was to promote the use of ICT as a tool in the intercultural teaching-learning process for the development of knowledge of second year elementary school students. In order to gather information for the elaboration of the theoretical framework, it is proceeded to research books and articles for its construction; On the other hand, the methodology used to carry out this project is framed within the interpretative paradigm that focuses on reflecting the reality of observable facts in a qualitative approach that aims at describing the qualities of the phenomenon. Besides, different types of research were used, such as: qualitative, descriptive and field research, which allowed obtaining data from the environment. It is important to emphasize that this research was based on the inductive method that starts from the most specific and goes to the general. The technique used was the structured interview directed to the authority, teacher and student. In addition, the results show that the role of technology and the Internet in the learning of Interculturality generates motivation in a positive and creative way that will serve to develop autonomous learning in students, getting attention, interest and motivation through the use of technological resources which will generate an impact on learning.